Hybrid fibre and free-space optical solutions in optical access networks - Mbah, Afamefuna Maduka (2016)
This thesis evaluates the potentials of hybrid fibre and free space optical (FSO) communications access networks in providing a possible solution to an all optical access network. In such network architectures, the FSO link can extend the system to areas where an optical fibre link is not feasible, and/or provide limited mobility for indoor coverage. The performance of hybrid fibre and FSO (HFFSO) networks based on digital pulse position modulation (DPPM), for both the indoor and outdoor environments of the optical access network, are compared with the performance of such a network that is based on conventional on-off keying non-return-to-zero (OOK NRZ) modulation using results obtained through computational and analytical modelling. Wavelength division multiplexing (WDM) and/or code division multiple access (CDMA) are incorporated into the network for high speed transmission and/or network scalability. The impacts of optical scintillation, beam spreading and coupling losses, multiple access interference (MAI), linear optical crosstalk and amplified spontaneous emission noise (ASE) on the performance of hybrid fibre and FSO (HFFSO) access networks are analysed, using performance evaluation methods based on simple Gaussian approximation (GA) and more complex techniques based on moment generating function (MGF), including the Chernoff bound (CB), modified Chernoff bound (MCB) and saddlepoint approximation (SPA). Results in the form of bit error rate (BER), power penalty, required optical power and outage probability are presented, and both the CB and MCB, which are upper bounds, are suggested as safer methods of assessing the performance of practical systems. The possibility of using a CDMA-based HFFSO network to provide high speed optical transmission coverage in an indoor environment is investigated. The results show a reduction in transmit power of mobile devices of about 9 – 20 dB (depending on number of active users) when an optical amplifier is used in the system compared to a non-amplified system, and up to 2.8 dB improvement over OOK NRZ receiver sensitivity is provided by a DPPM system using integrate and compare circuitry for maximum likelihood detection, and at coding level of two, for minimum bandwidth utilization. Outdoor HFFSO networks using only WDM, and incorporating CDMA with WDM, are also investigated. In the presence of atmospheric scintillations, an OOK system is required (for optimum performance) to continuously adapt its decision threshold to the fluctuating instantaneous irradiance. This challenge is overcome by using the maximum likelihood detection DPPM system, and necessitated the derivation of an interchannel crosstalk model for WDM DPPM systems. It is found that optical scintillation worsens the effect of interchannel crosstalk in outdoor HFFSO WDM systems, and results in error floors particularly in the upstream transmission, which are raised when CDMA is incorporated into the system, because of MAI. In both outdoor HFFSO networks (with WDM only and with WDM incorporating CDMA), the optical amplifier is found necessary in achieving acceptable BER, and with a feeder fibre of 20 km and distributive FSO link length of 1500 m, high speed broadband services can be provided to users at safe transmit power at all turbulence levels in clear air atmosphere.